Fuzzy Logic Simulation As a Teaching-Learning Media for Artificial Intelligence Class - Dewi, Tresna; Risma, Pola; Oktarina, Yurni (Journal of Automation, Mobile Robotics and Intelligent Systems, 2018)
Polytechnic as a vocational education has to keep updadang its curriculum with innovation and the latest technology application in industry and domestic. Teaching learning process in the classroom also has to be based on technology application. The teachinglearning process will be more effectie and interesting by involving the students to be more pro- actie and creatie. To engage the students more, the teacher needs a teaching-learning media, and one of these media is simulation software. The visualization of the simulation attracts students’ interest and enhances students’ creatiity. This paper proposes the application of an open source and low-cost sofware simulation as a teaching-learning media to create an interactive and exciting robotics class. This study will show the design and application of fuzzy logic controller in a mobile firefighter robot, and simulate the design in SCILAB, an open source sofware, and in MobotSim, a low-cost sofware. This alternative of open source software can be as good as the high- end ones. This paper shows that the application of fuzzy logic controller can be fun and variant for students to enjoy the class. The contribution of this research is to show and encourage teachers and students to learn robotics and artificial intelligence in an interactive classroom using free software and also encourage them to search more alternative open source sofware.